'How do you get to Tim Hortons?' Direction-giving in Ontario dialects. (March 2021) - Schlegl, Lisa; Tagliamonte, Sali A.
Abstract: In this study, we target the speech act of direction-giving using variationist sociolinguistic methods within a corpus of vernacular speech from six Ontario communities. Not only do we find social and geographical correlates to linguistic choices in direction-giving, but we also establish the influence of the physical layout of the community/place in question. Direction-giving in the urban center of Toronto (Southern Ontario) contrasts with five Northern Ontario communities. Northerners use more relative directions, while Torontonians use more cardinal directions, landmarks, and proper street names – for example, Go east on Bloor to the Manulife Centre . We also find that specific lexical choices (e.g., Take a right vs. Make a right ) distinguish direction-givers in Northern Ontario from those in Toronto. These differences identify direction-giving as an ideal site for sociolinguistic and dialectological investigation and corroborate previous findings documenting regional variation in Canadian English.